Reduction of systemic inflammation by elexacaftor/tezacaftor/ivacaftor correlates with lung function improvement in cystic fibrosis - Halle, Olga; Graeber, Simon Y.; Kontsendorn, Julia; Kessemeier, Claudia; Falke, Jan-Niklas; Schwabe, Jannik; Schütz, Katharina; Pallenberg, Sophia T.; Dalferth, Rebecca; Grychtol, Ruth; Ringshausen, Felix C.; Stahl, Mirjam; et al. (The European respiratory journal, 2025)
Background: The triple cystic fibrosis transmembrane conductance regulator modulator therapy elexacaftor/tezacaftor/ivacaftor (ETI) rapidly improves airway and systemic inflammation in people with cystic fibrosis. However, longitudinal effects on systemic inflammation and their relationship to lung function remain unknown. Methods: In this prospective, observational, multicentre study, we analysed peripheral blood neutrophil counts, C-reactive protein (CRP) and six pro-inflammatory serum cytokines in a cohort of 198 people with cystic fibrosis aged ≥6 years at baseline and follow-up visits 3, 12 and 24 months after initiation of ETI, compared to 74 age-matched healthy control participants. Results: Neutrophil counts and CRP, granulocyte colony-stimulating factor, interleukin (IL)-1β, IL-6 and IL-8 were reduced to 71%, 40%, 41%, 63%, 46% and 81% of median baseline values, respectively, after 3 months of therapy (all p<0.05), whereas monocyte chemotactic protein-1 reached 82% of baseline levels at 12 months only (p<0.05). Change from baseline to 3 months correlated with improvements in percent predicted forced expiratory volume for all systemic inflammation parameters except IL-8 (Spearman's r −0.17 to −0.42, p<0.05). All cytokines reached healthy control levels at or before 24 months. Decreased inflammation levels were sustained until 24 months for all parameters (p<0.05) except IL-6. Conclusions: Our results demonstrate that ETI exerts rapid and sustained effects on systemic inflammation associated with lung function improvements in children, adolescents and adults with cystic fibrosis in a real-world, post-approval setting. However, our data also show that individual markers of systemic inflammation remain at levels above those of healthy controls, particularly in certain subgroups, suggesting persistence or resurgence of residual systemic inflammation.
Online veröffentlicht: 4. Dezember 2025
Gesehen am 19.02.2026